QUALITATIVE ANALYSIS OF HIGH GRADE NANOSILICON OBTAINED FROM COASTAL LANDFORM IN ESE ODO LOCAL GOVERNMENT AREA OF ONDO STATE, NIGERIA - Oluyamo, Sunday Samuel; Famutimi, Olalekan Femi; Olatona, G. I.; Popoola, Adewumi Isaac; Olusola, Olajide Ibukun-Olu (FUDMA JOURNAL OF SCIENCES, 2023)
The research focused on the qualitative analysis of high grade nanosilicon obtained from coastal landform in Ese Odo Local Government Areas of Ondo State, Nigeria. The landform in the study areas were noted to possess different colours with appearances and physical presentation presumably of silicon content. The Silicon from the landform were obtained using magnesium as a reducing agent. The results of the energy dispersive x-ray (EDX) analyses of the samples ball-milled for 24 hours revealed that silicon has the highest percentage of all the elements observed in the spectra. The morphology of nanosilicon from Pekehan revealed the presence of agglomeration of irregular shaped particles with average particles sizes of 50.27 nm while Igbekebo and Oju-ala coastal landforms showed the presence of agglomerated ovoid shape with average particle sizes of 54.25 nm and 53.52 nm respectively. The X-ray Diffraction (XRD) spectral of the nanosilicon shows sharp distinct peaks which indicate crystalline nature of the samples. Based on the results obtained, it can be concluded that, the percentage of nanosilicon values obtained ranges between 68.85% to 73.03% which are relatively high enough and can find suitable industrial applications in sectors like the lithium-ion battery, biomedical devices, photovoltaic/solar cell and computer industries etc.